Muhammad Basiuni Imran: Tokoh Legendaris Islam, Sambas, Kalimantan Barat Abad 20 M - Wendi Parwanto (Fakultas Ushuluddin dan Dakwah Institut Ilmu Al-Qur'an (IIQ) Jakarta, Indonesia, 2023)
Research on ulama in West Borneo is important because it hasn’t been widely studied by researchers. Based on these reasons, the researcher is interested in studying this theme further. ‎This study uses the genealogy of knowledge theory and with a historical approach. The ‎conclusion of this article is a‎ Muhammad Basiuni Imran's thoughts were much influenced by Muhammad Rasyid Ridha in particular the idea of ​​Islamic reform, and these ideas were accentuated in the Sambas region, especially in reforming education.